The Influence of Online Customer Reviews and Online Customer Ratings on Purchasing Decisions for Cosmetic and Skincare Products via Sociolla E-Commerce - Intan Rizkia; Rusminah HS (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The purpose of this study is to determine the influence of online customer reviews and online customer ratings on purchasing decisions for cosmetic and skincare products through Sociolla E-Commerce. This type of causal quantitative research uses PLS-SEM, with a population of Sociolla consumers in Mataram and a sample of 100 respondents through purposive sampling. The instrument in the form of a 5-point Likert questionnaire was analyzed with SmartPLS after validity and reliability tests. The results of the study indicate that online customer reviews have a positive and significant effect on purchasing decisions, online customer ratings are also proven to have a positive and significant effect on purchasing decisions. Online customer reviews and online customer ratings have a contribution of 0.633 and an adjusted R-square of 0.626 or 62.6% in forming purchasing decisions and the remaining 36.7% is determined by other variables outside the research model.